A Phase I study to determine the pharmacokinetic profile, safety and tolerability of sildenafil (Revatio®) in cardiac surgery: the REVAKI‐1 study. (1st December 2016) - Ring, Arne; Morris, Tom; Wozniak, Marcin; Sullo, Nikol; Dott, William; Verheyden, Veerle; Kumar, Tracy; Brunskill, Nigel; Vaja, Rakesh; Murphy, Gavin J.
Abstract : Aims: Acute kidney injury (AKI) is a common and severe complication of cardiac surgery. There is no effective prevention or treatment. Sildenafil citrate (Revatio ®, Pfizer Inc.), a phosphodiesterase type 5 inhibitor, prevents post cardiac surgery AKI in pre‐clinical studies, however its use is contraindicated in patients with symptomatic cardiovascular disease. The aim of this study is to assess the safety and pharmacokinetics of intravenous sildenafil in cardiac surgery patients. Methods: We conducted an open label, dose escalation study with six patients per dose level. The six doses were 2.5 mg, 5 mg or 10 mg as a bolus, either alone or followed by an additional 2 h infusion of 2.5 mg sildenafil. Results: Thirty‐six patients entered the trial, of which 33 completed it. The mean age was 69.9 years. One patient died during surgery, two others were removed from the trial before dosing (all at dose level 5 mg + 2.5 mg). The pharmacokinetic profile of sildenafil was similar to previously published studies. For a dose of 10 mg administered as a bolus followed by 2.5 mg administered over 2 h the results were AUC∞ 537 ng h ml −1, C max 189.4 ng ml −1 and t 1/2 10.5 h. The drug was well tolerated with no serious adverse events related to drug administration. Higher sildenafil doses stabilized post‐surgery nitric oxide bioavailability. Conclusions: Pharmacokinetics of sildenafil during cardiopulmonary bypass were comparable to those of other patient groups. The drug was well tolerated at therapeutic plasma levels. These results support the further evaluation of sildenafil for the prevention of AKI in cardiac surgery.